2019
DOI: 10.1093/nar/gkz886
|View full text |Cite
|
Sign up to set email alerts
|

MSDB: a comprehensive, annotated database of microsatellites

Abstract: Microsatellites are short tandem repeats of 1–6 nucleotide motifs, studied for their utility as genome markers and in forensics. Recent evidence points to the role of microsatellites in important regulatory functions, and their length polymorphisms at coding regions are linked to various neurodegenerative disorders in humans. Microsatellites show a taxon-specific enrichment in eukaryotic genomes, and their evolution remains poorly understood. Though other databases of microsatellites exist, they fall short on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 23 publications
0
21
0
5
Order By: Relevance
“…We next aimed to harness the information from our high-throughput assay to examine the impact of DNA polymerase stalling at STRs on their genomic representation. Using data from the MicroSatellite DataBase [ 3 ] reporting ~ 4,500,000 STR loci within the human genome, we found that the relative abundance of each of the 501 unique double-stranded motifs directly anticorrelates with the ability of the motif to stall DNA polymerase (Fig. 5 a) suggesting that STRs capable of significant secondary structure are deleterious.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We next aimed to harness the information from our high-throughput assay to examine the impact of DNA polymerase stalling at STRs on their genomic representation. Using data from the MicroSatellite DataBase [ 3 ] reporting ~ 4,500,000 STR loci within the human genome, we found that the relative abundance of each of the 501 unique double-stranded motifs directly anticorrelates with the ability of the motif to stall DNA polymerase (Fig. 5 a) suggesting that STRs capable of significant secondary structure are deleterious.…”
Section: Resultsmentioning
confidence: 99%
“…Genomic coordinates of STRs from 6 eukaryotic genomes were recovered from the MicroSatellite DataBase [3]. The analysed genomes were Homo sapiens (hg38), Mus musculus (mm10), Gallus gallus (galGal6), Danio rerio (dm6), Drosophila melanogaster (dm6) and Saccharomyces cerevisiae (sacCer3).…”
Section: Abundance and Length Of Eukaryotic Strsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we downloaded the virus integration site information from the VISDB(Tang et al, 2020) and we lifted it over to the hg19 version using the liftover tool from the UCSC Genome Browser since FusionAI’s training was done based on the sequence of hg19 version (Navarro Gonzalez et al, 2021). We integrated 13 types of repeats (Alu repeats, A-Phased repeats, Directed repeats, DNA transposons, “G-Quadruplex, forming repeats”, Inverted repeats, L1 repeats, L2 repeats, “Low_complexity, A/T rich regions”, Microsatellites, MIR repeats, Mirror repeats, and Z-DNA motifs) from RepeatMasker (Bao et al, 2015) and MicroSatellite DataBase (MSDB) (Avvaru et al, 2020). For the diverse types of structural variants including the copy number variants, we downloaded the arranged breakpoint information of the structural variants from dbVar (Lappalainen et al, 2013).…”
Section: Methods Detailsmentioning
confidence: 99%
“…There is an abundance of exceptionally long (≥ 6 repeats) STRs in the core promoter regions of human protein-coding genes, and many of these appear to be evolutionarily conserved (Ohadi, Mohammadparast, & Darvish, 2012). Microsatellites show a taxon-specific enrichment in eukaryotic genomes (Avvaru, Sharma, Verma, Mishra, & Sowpati, 2019). It is also known that transcription factor binding sites (short motifs) tend to cluster in tandem (homotypic regulatory clusters), and the repeating nature of these motifs would be expected to contribute to dependencies between positions over short ranges (Lifanov, Makeev, Nazina, & Papatsenko, 2003;Papatsenko et al, 2002).…”
Section: Introductionmentioning
confidence: 99%